Quality of delivery of the Standard Days Method as compared with contraceptive pills in Rwanda. Issue 4 (1st October 2006) - León, Federico R; Blair, Caroline; Lundgren, Rebecka; Jennings, Victoria; Huapaya, Ana; Mukabatsinda, Marie; Muramutsa, Félix
Abstract : Background and methodology: Replicating a Peruvian study, this research introduced the Standard Days Method (SDM) into Rwanda Ministry of Health clinics and evaluated client counselling on the new method against that given for contraceptive pills. Providers received technical reinforcement concerning established methods in addition to SDM training. To evaluate their quality of care, simulated clients implemented a service test in visits to 20 clinics. Results: As in Peru, providers exchanged significantly more relevant information with clients who chose SDM than with those who chose pills. Also, a minority of providers posed barriers to SDM access by refusing to give SDM tools to the client until she brought her partner for consultation. Conclusions: The findings of this study confirm that SDM counselling is generally satisfactory, although SDM training needs adjustment, and that the rigour of providers' pill counselling remains below capacity.